Group Behavior in Organizational Culture and Inclusive Leadership in Multicultural Islamic Educational Institutions - Eka Karmila; Yeni Januarni; Kasinyo Harto; Tutut Handayani (International Journal of Education and Literature, 2025)
This study is grounded in the importance of understanding the dynamics of group behavior within multicultural Islamic education institutions , where spiritual values , organizational culture , and leadership interact to create a harmonious working climate . A strong organizational culture and inclusive leadership are believed to be the foundation for fostering collaboration , fairness , and mutual respect among members . The purpose of this study is to analyze how organizational culture and inclusive leadership styles shape group behavior within socially and culturally diverse Islamic education contexts . This research employs a qualitative method with a Systematic Literature Review (SLR) approach , reviewing relevant academic literature focused on group dynamics , work culture , and Islamic values . The findings indicate that an Islamic value - based organizational culture and inclusive leadership play a significant role in strengthening social cohesion , enhancing participation , and fostering group behavior that is both collaborative and spiritually meaningful .